Burnout, Engagement, and Dental Errors Among U.S. Dentists. Issue 8 (December 2021) - Yansane, Alfa; Tokede, Oluwabunmi; Walji, Muhammad; Obadan-Udoh, Enihomo; Riedy, Christine; White, Joel; Kalenderian, Elsbeth
Abstract : Background: Errors can happen during patient care, and some result in harm to the patient. Work place stress has been well established in dentistry, but its relation with errors in the delivery of patient care is less understood. The authors evaluated the relationship between burnout, work engagement, and self-reported dental errors among American dentists. Methods: From May to August 2016, a national sample of American Dental Association member dentists were sent a validated, electronic survey assessing their levels of burnout, work engagement, and dental errors. Results: Of the 391 responding dentists, 46.1% reported concern that they had made a dental error in the last 6 months, 12.1% of the dentists were informed by dental staff that they may have committed an error in the last 6 months, 16% were concerned that a malpractice lawsuit would be filed against them, and 3.6% were actively involved in a malpractice lawsuit. In the adjusted analysis, multivariate logistic regression showed that dentists with either high burnout risk were more likely to report concern over a perceived error within the last 6 months. Conclusions: The results suggest that dental provider burnout is potentially a key predictor of reporting perceived dental errors. It is imperative that the dental profession continue to study the effects of work-related stress, develop professional practices that decrease burnout, and reduce errors. Practical Implications: Efforts that minimize the potential for burnout may help reduce the occurrence of errors and improve the quality of care provided to dental patients.